2009
DOI: 10.1038/cgt.2009.48
|View full text |Cite
|
Sign up to set email alerts
|

Heat-induced transcription of diphtheria toxin A or its variants, CRM176 and CRM197: implications for pancreatic cancer gene therapy

Abstract: Vectors combining the heat shock proteins (HSPs) promoter with the catalytic subunit A of the diphtheria toxin (DTA) or its variants, cross-reacting material (CRM) 176 and 197, were engineered to investigate the effect of bacterial toxins on pancreatic cancer (PC) cells. Three heat-inducible enhanced green fluorescent protein (eGFP)-expression vectors were obtained: V1 (91% homology to HSPA6), V2 (five heat shock elements upstream the minimal HSPA6 promoter) and V3 (V1 and V2 combined). The highest eGFP transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 46 publications
1
6
0
1
Order By: Relevance
“…Because of its easy, safe preparation, this delivery vector can be useful in delivering small amounts of pancreatic cancer's new treatments. These treatments include vectors combining the heat shock proteins (HSPs) promoter with the catalytic subunit A of the diphtheria toxin (DTA) or its variants which were engineered to investigate the effect of bacterial toxins, with lethal effects, on pancreatic cancer cells 19 . Considering the advantages of this delivery system, it should be a useful approach to plasmid-based gene transfer for pancreatic cancer local therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its easy, safe preparation, this delivery vector can be useful in delivering small amounts of pancreatic cancer's new treatments. These treatments include vectors combining the heat shock proteins (HSPs) promoter with the catalytic subunit A of the diphtheria toxin (DTA) or its variants which were engineered to investigate the effect of bacterial toxins, with lethal effects, on pancreatic cancer cells 19 . Considering the advantages of this delivery system, it should be a useful approach to plasmid-based gene transfer for pancreatic cancer local therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that cytosolic expression of the diphteria toxin A (DT-A) fragment resulted in tumor cell death. 23,24) Even cytosolic expression of the DT-A fragment mediated by a baculovirus gene therapy vector inhibited the proliferation of malignant glioma cells. 25) Furthermore, the A1 fragment has been found to exert antiviral effects on various ruminant viruses such as bovine leukemia virus (BLV), bovine retroviruses, and bovine immunodeficiency virus (BIV), [26][27][28][29] similarly to its inhibitory effects on baculoviruses, observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Por ejemplo, se ha utilizado el promotor de la familia de proteínas heat shock 70 (HSP70) en conjunto con el gen de la cadena A como posible tratamiento para el cáncer de páncreas. Este promotor es útil ya que HSP70 es expresada por las células del cáncer de páncreas, se puede activar la expresión por calor, es muy eficiente (impidiendo el crecimiento celular en el 100% de células transfectadas) y se puede controlar de forma espacial focalizando la fuente de calor en el sitio del tumor (31). Esta metodología ha sido usada con éxito para tratar casos de cáncer de páncreas consiguiéndose resultados prometedores in vivo (31).…”
Section: Toxina De La Difteriaunclassified